DETERMINATION OF SHELF-LIFE OF JABOTICABA´S FRUITS CV. ’SABARÁ’ - Henrique, C.M.; Prati, P.; Parisi, M. M. C.; Tavares, S. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The jaboticaba is a fruit tree with great potential, both for fresh consumption, as for industrialization. The objective of this study was to evaluate the shelf-life of jaboticabas’s fruits cv. ’Sabará’ stored under refrigeration and at room temperature. After harvest, the fruits were washed, screened, packed in plastic trays, in single layer, and stored under refrigeration (5 °C, and 49% UR), and at room temperature (27 ºC, and 33% UR). The determinations performed in triplicate immediately after harvest and every other day, until the disposal of the fruit, were: pH, soluble solids (°Brix), total titratable acidity (% citric acid), total and reducer sugars (%), vitamin C (mg/100g) and phytopathological. The design adopted was entirely randomized, realized the analysis of variance (F test) and comparison of averages by Tukey test to 5% of significance. Under refrigeration, the storage was more than 9 days to 12 days, the fruits showed intense shriveling (loss of moisture), being unsuitable for marketing. The soluble solids remained stable during this period, but there was decrease of pH and the levels of total and reducer sugars, in addition to increased acidity, facts that indicate occurrence of fermentation process. The losses of vitamin C were of the order of 72,5, from 4,952mg/100g in zero time, and 3,593mg/100g at the end of this period. The stored fruits at room temperature were discarded at the beginning of storage, by shriveling, incidence of microorganisms and strange odor.